An ultrasonic system for profiling bubblers in water - Ibrahim, Sallehuddin; Faramarzi, Mahdi; Md Yunus, Mohd Amri; Abdul Rahim, Ruzairi (Penerbit UTHM, 2020)
Multi-phase flow occurs as two or more discrete phases flow in a closed pipe or a vessel. Examples of phases include gas, liquid or solid and also different immiscible liquids or solids[1]. Two phase flow of fluids (e.g. gas/liquid, liquid/liquid, etc.) is an important phenomenon in which two immiscible phases coexist in a thermodynamic equilibrium. As a two phase flow regime, bubbly flow column are intensively used as multiphase contactors and reactors in chemical, biochemical and petrochemical industries. Investigation of design parameters characterizing the operation and transport phenomena of bubble columns have led to better understanding of the hydrodynamic properties, heat and mass transfer mechanisms and flow regime characteristics ongoing during the operation[2, 3]. Due to the stringent regulations on precise flow control especially in the case of two phase fluid flow,, there has always been a necessity for developing an easier to use, yet more precise approaches or instrumentation. Accordingly, tomographic measurement is more significant and attractable especially in today's industrial process ..